"I only watch for the commercials": Messages about weight, eating and race in Super Bowl advertisements. Issue 11 (22nd September 2017) - Lydecker, Janet A.; Izzo, Antonio; Spielberger, Gail; Grilo, Carlos M.
Summary: Objective: Health experts and communication experts assert that the media influence individuals' health. Yet, incongruously, the public, policy‐makers and the media themselves appear reticent to accept that the media could have extensive negative influence on health. Methods: The current study examined all ads that aired from Super Bowl XLVI through Super Bowl XLIX (N   =   241) using a detailed, multistep coding process. Results: Ads had similar racial/ethnic diversity in the full sample and food/beverage ads. A minority (14.5%) of advertisements contained actors with overweight/obesity, who were more likely to be White and less likely to be Hispanic compared with race/ethnicity in all ads. Humour and tone were similarly present whether or not the ads included actors with overweight/obesity. Conclusions: Findings are striking given the high prevalence of overweight/obesity in the USA, particularly among Black and Hispanic populations, and the comparatively low representation of actors with overweight/obesity in Super Bowl advertisements. Surprising weight findings may signal a change in how the media portray body‐size norms (away from exclusively thin), although representations remain disproportionate from actual body‐size distributions in the USA.